Prevalencia de preeclampsia y eclampsia en pacientes entre 20 y 30 años. Hospital General Ambato, 2019 - Cachiguango Yacelga, Héctor Alex (2019)
Introduction: The world health organization considers that the main complications that cause maternal deaths are: severe hemorrhages mostly after childbirth, infections, gestational hypertension (preeclampsia and eclampsia), birth complications and dangerous abortions. Course objective: To determine the prevalence of preeclampsia and eclampsia in patients between 20 and 30 years. Ambato General Hospital, 2019. Material and methods: An inductive, deductive and documented review study was conducted. The pregnant women treated between January and July of 2019, between the ages of 20 and 30, who were hospitalized in the Gynecology and Obstetric service, were investigated, having a sample of 303 patients, suffering the medical records found in the Statistical database General Hospital Ambato. Results: The number of previous parts of pregnant women with preeclampsia and / or eclampsia is shown in table 7, in which we can observe, as significant data, 14 nulliparous patients with a percentage of 62%, continuing with 8 mutigest patients with a percentage 38% and no large multi-patient patient. This is significant since it agrees with one of the risk factors studied internationally and we can say that we have to give greater control to the primigests. Conclusions: Of 303 pregnant women between the ages of 20 and 30 who correspond to 100%, of which 21 develop preeclampsia, that is 7%, of these 71% develop preeclampsia without signs of severity and 29% develop preeclampsia with Signs of severity and no eclampsia development.